Mycorrhization alters foliar soluble amino acid composition and influences tolerance to Pb in Calopogonium mucunoides - Souza, Lucas Anjos; Camargos, Liliane Santos [UNESP]; Schiavinato, Marlene Aparecida; Lopez Andrade, Sara Adrian (Brazilian Soc Plant Physiology, 2014)
Soil contamination by lead (Pb) is a problem due to the persistence of this element on soil. High amounts of Pb in soil impair plant establishment, however some plants may increase tolerance to heavy metals when colonized by arbuscular mycorrhizal fungi (AMF). The leguminous plant, Calopogonium mucunoides, is Pb-sensitive that is tolerant to Pb when associated to AMF. We performed a chromatographic analysis of foliar free-amino acid in non-mycorrhizal and mycorrhizal plants to determine its relation with Pb tolerance. Mycorrhization caused drastic increase in aspartate, glutamine, glycine, threonine, alanine, isoleucine and gamma-aminobutiric acid (GABA), while depletion of asparagine, histidine and arginine was observed in AMF-associated plants. When grouped according to common metabolic precursor, it was found that amino acids derived from 3-phosphoglicerate and pyruvate was higher in mycorrhizal plants while amino acids derived from glucose-6-phosphate and 2-oxoglutarate were higher in nonmycorrhizal plants; phosphoenolpyruvate and oxaloacetate pathways were not influenced by mycorrhization. Summarizing, mycorrhization changed soluble amino acids profile in C. mucunoides leaves, especially aspartate, alanine and GABA, which may be involved in tolerance to abiotic stress. Additionally the depletion of asparagine, histidine and arginine may be related to a deviation for metabolic pathways not related to protein biosynthesis but to the synthesis of polyamines, especially in the case of arginine. Therefore, we suggest that mycorrhization influence on soluble free amino acid profile in leaves can be one of the factors involved with the attenuation of Pb toxicity in AMF-associated C. mucunoides plants.
Keywords: Heavy metal; Lead; Metabolites; Metal-tolerance